Psychology Meets Archaeology: Psychoarchaeoacoustics for Understanding Ancient Minds and Their Relationship to the Sacred - Valenzuela, Jose; Díaz-Andreu, Margarita; Escera, Carles (Frontiers in Psychology, 2020)
How important is the influence of spatial acoustics on our mental processes related to sound perception and cognition? There is a large body of research in fields encompassing architecture, musicology and psychology that analyses human response, both subjective and objective, to different soundscapes. But what if we want to understand how acoustic environments influenced the human experience of sound in sacred ritual practices in premodern societies? Archaeoacoustics is the research field that investigates sound in the past. One of its branches delves into how sound was used in specific landscapes and at sites with rock art, and why past societies endowed special significance to places with specific acoustical properties. Taking advantage of the advances made in sound recording and reproduction technologies, researchers are now exploring how ancient social and sacred ceremonies and practices related to the acoustic properties of their sound environment. Here we advocate for the emergence of a new and innovative discipline, experimental psychoarchaeoacoustics. We also review underlying methodological approaches and discuss the limitations, challenges and future directions for this new field.